2018
DOI: 10.1186/s41983-018-0019-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of stroke outcome: the role of hemorheology, natural anticoagulants, and serum albumin

Abstract: BackgroundThe early hours after an acute stroke are crucial; early accurate prediction of outcome in stroke patients can help health system providers and families to choose appropriate lines of management and plan for the future. The aim of this work is to assess the role of hemorheological parameters (such as blood viscosity, hematocrit, platelet aggregation, and leukocyte count), protein C, protein S, antithrombin III, and serum albumin as predictors of stroke outcome.MethodsThirty subjects, 20 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…Global sensitivity analysis indicated that albumin plays an important role in the prognosis of acute stroke. Hashem et al [ 36 ], Aquilani et al [ 37 ], and Xu et al [ 38 ] reported that the high dose of albumin positively affects the prognosis of ischemic stroke patients, which were consistent with the results of this study. Albumin is often regarded as a marker of nutritional status and a negative phase protein that decreases in concentration during injury [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Global sensitivity analysis indicated that albumin plays an important role in the prognosis of acute stroke. Hashem et al [ 36 ], Aquilani et al [ 37 ], and Xu et al [ 38 ] reported that the high dose of albumin positively affects the prognosis of ischemic stroke patients, which were consistent with the results of this study. Albumin is often regarded as a marker of nutritional status and a negative phase protein that decreases in concentration during injury [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…An increase in the levels of hemorheological indicators is one critical risk factor for stroke [ 56 , 57 ]. Abnormalities in hemorheology have an important impact on the formation of blood clots, and whole blood viscosity, PV, and FIB are all important indicators reflecting hemorheology.…”
Section: Discussionmentioning
confidence: 99%
“…The early hours after an acute stroke are crucial; it is the most useful time for effective management. With the rising burden of stroke and marked heterogeneity in stroke manifestation and outcome, it is necessary to find accurate, reliable, and simple predictors of functional recovery [12]. Accumulating evidences suggest that oxidative stress and inflammation play a crucial role in the pathophysiology of acute ischemic stroke [13].…”
Section: Discussionmentioning
confidence: 99%